Study and Implementation of Internet of Things (IoT) Based on Rainwater Sensor Using Arduino through Mobile Application - Malathy, Batumalay; Rubinyaa, Sekar; Chitra, Batumalai (INTI International University, 2019)
Rain is very important to our ecosystem and has many benefits such as generating energy through hydropower. Internet of Technology draw much attention with various monitoring capabilities into current building such as houses. Arduino is a device to interface between a microcontroller and sensors. The combination of Arduino, rainwater sensor and mobile application in this system can help to alert people when it is raining. The system ensure the LED and buzzer is activated when it’s raining and to enable user to connect their mobile application with the rainwater sensor system and control it by just clicking on the buttons available in the mobile application. Upon receiving the signals from this system, user should be aware of rain and take the necessary steps to collect the rainwater.